Fundamentals of Entrepreneurship (ENT300) : Kidz Paradize / Nur Imannina Ibrahim … [et al.] - Ibrahim, Nur Imannina; Shazali, Nur Ain Atirah; Abdul Rahman, Nur Azzah Syahirah; Burhaniza, Zaidatul Amira; Khamizan, Muhammad Fitri (2018)
Kidz Paradize have been recognized by citizens in Kuching. This is due to the location which is inside The Spring Shopping Mall where the place for the society spending their time. This place is focusing on the children. So, most of the parents who is spending their time in this shopping mall can bring their child to play at Kidz Paradize. Service offered by Kidz Paradize is playground, study room, small café and many more. The major problem faced by Kidz Paradize is the way to handle the child. It is because, they need to focus on the child while they are playing inside it. Some of the children are not easy to handle because something they thought that they just can be handle by their parents. Some of the children also naughty because they know that they only want to play with the other children. Kidz Paradize also faced with their competitors which is ‘Molly Fantasy'. The competitors like to set a lower price compared to price set by Kidz Paradize. But, the price set by Kidz Paradize show the quality of the service and places provide.